Jovens de partido: práticas políticas no Partido dos Trabalhadores de São Paulo - 2012 e 2013 - Victal, Maria Imaculada Fernandes (2017)
This thesis is inside of the emerging field of youth studies in Brazil and Latin America. It talks about the political theme and practices of young political-partisan militants form a working group within the Workers' Party (PT), in the city of São Paulo, between 2012 and 2013. Its research problem is geared towards the search for the characterization of youth participation in political parties at this time of contemporaneity and the questioning of political and party institutions. Based on a discussion that articulates Anthropology, Sociology and Politics, what is highlighted in the analysis of these practices are the values and the meanings of what is experienced in the political-partisan space and how the particular ways of seeing the world act in the political consciousness of this contemporary youth, which, at the moment, is part of the hegemonic political force in Brazil. The qualitative ethnographic perspective - based on participant observation, prolonged coexistence with the object of studies and immersion in the cultural universe investigated - is taken as a privileged methodological framework for field research. The theoretical framework of references is anchored in Gramsci (1999), Martín-Barbero (1978, 1998, 2004), Williams (1969, 1979, 1992, 2011) and in contemporary Brazilian and Latin American authors who have legitimacy in the debate about young and youth: Alvorado (2012, 2014), Borelli (2008, 2009, 2012), Vommaro, (2012, 2013, 2015)